Electrospinning of recycled PET to generate tough mesomorphic fibre membranes for smoke filtration. Issue 4 (4th December 2014) - Strain, I. N.; Wu, Q.; Pourrahimi, A. M.; Hedenqvist, M. S.; Olsson, R. T.; Andersson, R. L.
Abstract : Regeneration of used pet bottles via electrospinning, into high performance membranes for smoke filtration. Abstract : Tough fibrous membranes for smoke filtration have been developed from recycled polyethylene terephthalate (PET) bottles by solution electrospinning. The fibre thicknesses were controlled from 0.4 to 4.3 μm by adjustment of the spinning conditions. The highest fibre strength and toughness were obtained for fibres with an average diameter of 1.0 μm, 62.5 MPa and 65.8 MJ m −3, respectively. The X-ray diffraction (XRD) patterns of the fibres showed a skewed amorphous halo, whereas the differential scanning calorimetry (DSC) results revealed an apparent crystallinity of 6–8% for the 0.4 and 1 μm fibres and 0.2% crystallinity for the 4.3 μm fibres. Heat shrinkage experiments were conducted by exposing the fibres to a temperature above their glass transition temperature ( T g ). The test revealed a remarkable capability of the thinnest fibres to shrink by 50%, which was in contrast to the 4.3 μm fibres, which displayed only 4% shrinkage. These thinner fibres also showed a significantly higher glass transition temperature (+15 °C) than that of the 4.3 μm fibres. The results suggested an internal morphology with a high degree of molecular orientation in the amorphous segments along the thinner fibres, consistent with a constrained mesomorphic phase formed during their rapid solidification in the electric field. Air filtration was demonstrated with cigarette smoke as a model substance passed through the fibre mats. The 0.4 μm fibres showed the most effective smoke filtration and a capacity to absorb 43× its own weight in smoke residuals, whereas the 1 μm fibres showed the best combination of filtration capacity (32×) and mechanical robustness. The use of recycled PET in the form of nanofibres is a novel way of turning waste into higher-value products.